2008
DOI: 10.1016/j.rgg.2007.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of local earthquakes in the crust beneath central Lake Baikal

Abstract: We have located earthquake hypocenters in the area of central Lake Baikal using the Hypoellipse inversion of direct P traveltimes collected by a local seismological network of seven stations in 2001 through 2005. The location accuracy depends on the agreement between the reference velocity model and the real subsurface. Traveltime residuals have no bearing on the accuracy of depth estimates due to origin time errors. Hypocenter location with reference to a DSS-derived layered velocity model pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 6 publications
0
6
0
3
Order By: Relevance
“…In some areas of interest to this paper other studies have used dense local seismograph networks to constrain the depth distribution of smaller events (e.g. Deverchere et al 1991; Avetisov 1993; Roecker et al 1993; Kovachev et al 1994; Schulte‐Pelkum et al 2005; Monsalve et al 2006; Xu et al 2006; Suvorov & Tubanov 2008) and these are discussed in each region, as appropriate.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In some areas of interest to this paper other studies have used dense local seismograph networks to constrain the depth distribution of smaller events (e.g. Deverchere et al 1991; Avetisov 1993; Roecker et al 1993; Kovachev et al 1994; Schulte‐Pelkum et al 2005; Monsalve et al 2006; Xu et al 2006; Suvorov & Tubanov 2008) and these are discussed in each region, as appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…To the west, in the Lake Baikal Rift, Radziminovitch et al (2005) and Suvorov & Tubanov (2008) found that the maximum hypocentral depths were at 25 km in south and central Lake Baikal. Suvorov & Tubanov (2008) also noted that only very rare unrepresentative events exceeded 22 km in depth. These values are shallower than that found by all local studies in the NE Rift, though still somewhat deeper than the earthquakes in Lake Baikal studied teleseismically (16 km).…”
Section: Extensionmentioning
confidence: 97%
See 2 more Smart Citations
“…Также при анализе сейсмичности отмечается наличие брешей в эпицентральном поле, чередование участков повышенной и пониженной плотности эпицентров землетрясений, коррелирующих с блоковой дели-мостью земной коры [Golenetsky, 1976;Solonenko et al, 1997;Zherebtsov, 2012;Radziminovich et al, 2018]. Основная масса землетрясений в районе Южнобайкальской впадины локализуется на глубинах 9-21 км, с максимумом на 14-18 км [Arefiev et al, 2008;Radziminovich, 2010;Suvorov, Tubanov, 2008].…”
Section: изучаемый регионunclassified